2022
DOI: 10.1093/cid/ciac004
|View full text |Cite
|
Sign up to set email alerts
|

Attributable Mortality of Candida Bloodstream Infections in the Modern Era: A Propensity Score Analysis

Abstract: Background This study quantifies the mortality attributable to Candida bloodstream infections (BSI) in the modern era of echinocandins. Design We conducted a retrospective cohort study of adult patients admitted to Barnes Jewish Hospital, a 1,368-bed tertiary care academic hospital, in Saint Louis, Missouri from 1/2/2012-4/30/2019. We identified 626 adult patients with Candida BSI that were frequency-matched with 6,269 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Candida -related infections are responsible for the high mortality rate of hospitalized patients ranging from 30 to 80% [ 29 , 30 ]. Bloodstream infections (candidemia) result in mortality of 30 to 60% of individuals [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Candida -related infections are responsible for the high mortality rate of hospitalized patients ranging from 30 to 80% [ 29 , 30 ]. Bloodstream infections (candidemia) result in mortality of 30 to 60% of individuals [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, there were no untreated episodes of candidemia, which have been associated with a mortality of nearly 70%. 24 A prior study reported that 14% of patients without an IDC were untreated. 21 This difference may be due to a more modern cohort in which clinicians are more likely to treat candidemia.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 The mortality rates associated with systemic Candida infections exceed 40% even with antifungal treatment. 1,6 Consequently, the World Health Organization (WHO) classified C. albicans, together with Candida auris, Cryptococcus neoformans, and Aspergillus fumigatus, as fungal pathogens requiring critical and most urgent attention. 7 Only three out of the four classes of antifungal drugs approved for use in the clinic are effective against candidaemia.…”
Section: ■ Introductionmentioning
confidence: 99%